An assessment of the intention to adopt blockchain technology (BCT) in SMEs: A South African Analysis - Anderson, Brain (University of the Witwatersrand, Johannesburg, 2023)
This study examines the factors influencing the intention to adopt blockchain technology (BCT) among small and medium-sized enterprises (SMEs) in South Africa. Despite the potential benefits of BCT, such as increased transparency, security, and efficiency, its adoption among businesses, especially SMEs in South Africa, is still relatively low. To address this gap, the study proposes a conceptual framework that extends the Technology Acceptance Model (TAM) by including both internal and external variables. The study hypothesizes that these variables influence SMEs' perceived usefulness and perceived ease of use of BCT, which, in turn, influences their intention to adopt the technology. The internal variables in the framework include innovativeness, self-efficacy, and perceived system complexity, while the external variables include strategic orientation and social influence. To test the hypotheses, the study collects data from a survey of SMEs in South Africa, using a structured questionnaire. The survey includes questions on the SMEs' familiarity with BCT, their perceptions of its benefits and drawbacks, and their intentions to adopt the technology. The data is analysed using structural equation modelling to test the relationships between the variables. The findings of the study suggest that SMEs' intentions to adopt BCT are influenced by their perceptions of the technology's usefulness and ease of use, as well as their innovativeness, self-efficacy, and perceptions of system complexity. The study also finds that external factors, such as strategic orientation and social influence, play a significant role in influencing SMEs' intentions to adopt BCT. Overall, the study contributes to the literature on BCT adoption by extending the TAM with internal and external variables that are specific to the South African context. The study's findings have practical implications for SMEs in South Africa that are considering adopting BCT, as it can help them understand the factors that influence their intentions to adopt the technology. The study also provides recommendations for researchers who are interested in promoting the adoption of BCT among SMEs in South Africa.
A research article submitted to the Faculty of Commerce, Law and Management, University of the Witwatersrand, in partial fulfillment of the requirements for the degree of Master of Business Administration Johannesburg, 2023
Keywords: Blockchain; intention; adopt; BCT; UCTD; SDG-9: Industry, innovation and infrastructure